Detection of neutralizing antibodies against arboviruses from liver homogenates. - Thaís Alkifeles Costa; Matheus Soares Arruda; Gabriela Fernanda Garcia-Oliveira; Erik Vinicius de Sousa Reis; Anna Catarina Dias Soares Guimarães; Gabriel Dias Moreira; Nidia Esther Colquehuanca Arias; Marina do Vale Beirão; Nikos Vasilakis; Kathryn A Hanley; Betânia Paiva Drumond (PLoS Neglected Tropical Diseases)
Yellow fever virus (YFV) circulates in a sylvatic cycle between non-human primates (NHPs) and arboreal mosquitoes in Brazil. Passive monitoring of ill or deceased NHPs is a key component of the Brazilian yellow fever (YF) surveillance program. Samples from NHPs carcasses are usually suitable for molecular tests but not for serological assays. As an alternative to the conventional plaque reduction neutralization test (PRNT) based on sera, we tested the utility of liver homogenates from experimentally infected (YFV, Mayaro virus [MAYV], chikungunya virus [CHIKV], or mock) mice to quantify PRNTs. Although homogenates from mock-infected mice showed a low level of nonspecific virus neutralization against all three viruses, homogenates from YFV-, MAYV- and CHIKV-infected mice demonstrated significantly higher levels of virus neutralization compared to controls. Receiver operating characteristic (ROC) curves analyses were performed using the median neutralization values of three technical replicates for each infected group separately or collectively. Results showed scores ≥0.97 (95% CI ≥ 0.89-1.0) for the area under the curve at dilutions 1:20 to 1:80, suggesting that median virus neutralization values effectively differentiated infected mice from controls. Liver homogenates obtained from 25 NHP carcasses (collected during the 2017 YF outbreak in Brazil) were also tested using the adapted PRNT as well as rapid lateral flow tests to investigate anti-YFV IgM. Neutralization activity was detected in six NHP samples that were also positive by PCR and anti-YFV IgM tests and one sample that tested negative by PCR and IgM test. Our results demonstrate the feasibility of using liver homogenates as an alternative approach for serological investigation in viral epidemiologic surveillance.